Analisa Usaha Ternak Domba dengan Pola Pemeliharaan Intensif dan Semi Intensif di Desa Suka Raya Kecamatan Pancur Batu - Fadli Hamsah; Nur Asmaq (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study aims to analyze the profitability and feasibility of sheep farming using intensive and semi-intensive rearing sistems in Suka Raya Village, Pancur Batu Sub-district. The research employed a survey method with purposive sampling, involving 16 farmers (8 intensive and 8 semi-intensive), each rearing more than 15 sheep and operating for at least 3 years. Data were collected through questionnaire interviews and field observations, then analyzed descriptively to calculate production costs, revenue, income, R/C ratio, and Break Even Point (BEP). Results showed that the average total production cost for the intensive sistem was Rp 52,429,313, higher than the semi-intensive sistem at Rp 39,664,375. The average revenue for the intensive sistem was Rp 69,150,000, while the semi-intensive sistem was Rp 63,712,500. The average income for intensive farmers was Rp 16,720,688, compared to Rp 24,048,125 for semi-intensive farmers. The average R/C ratio for the intensive sistem was 1 (near break-even), while the semi-intensive sistem was 2 (more efficient and profitable). BEP analysis indicated higher sales for the intensive sistem (Rp 844,022/sheep/period) compared to the semi-intensive sistem (Rp 691,052/sheep/period), with a larger production BEP for the intensive sistem (44 sheep) than the semi-intensive sistem (33 sheep). The semi-intensive sistem is recommended for farmers with limited capital and small to medium-scale operations due to lower costs and higher profit margins, while the intensive sistem is more suitable for large-scale operations with adequate capital, feed management, and health care.